Management of Salmonella Septic Bursitis in Renal Transplant Recipient - Prasetya, Albert; Ariane, Anna; Setyohadi, Bambang (Indonesian Rheumatology Association, 2018)
Salmonella as a causative agent in septic bursitis is considered rare. We report a case of 56 years old male with history of renal transplantation and using mycophenolate mofetil, cyclosporine and methylprednisolone as maintenance, admitted due to 3-week-fever associated with tenderness and swelling on left shoulder. Upon investigation, a diagnosis of septic bursitis was established. Salmonella enteritidis as the definitive causative agent was revealed. He was treated with meropenem 1g IV three times daily and levofloxacin 500 mg IV once a day for 3 weeks, followed by oral ciprofloxacin 500 mg twice a day for 2 weeks and oral metronidazole 500 mg three times a day for 1 week with a total duration of 5 weeks of antibiotics. On the subsequent follow up there was no recurrence episode of fever and the swelling of the left shoulder subsided, no tenderness noted and the patient has no limitation of range of movement. Since immunocompromised state complicates the management, the duration of therapy may twice longer than the typical management of septic bursitis. Salmonella as etiologic agent should be considered as differential in immunocompromised patient with septic bursitis.Keywords: Immunocompromised state, septic bursitis, deep bursae, Salmonella, duration of therapy.